1992
DOI: 10.1111/j.1365-2621.1992.tb08042.x
|View full text |Cite
|
Sign up to set email alerts
|

TBA Values, Sensory Characteristics, and Volatiles in Ground Pork During Long‐term Frozen Storage: Effects of Packaging

Abstract: Ground pork (30% fat) was packaged in,vacuum bags (V), polyvinyl chloride film (P\. Saran Wrao"M. aluminum foil (A\. or Saran"-.,I aluminum foil combination (S'A) g& frozen at -17"d f& 13, 26, and 39 wk. Samples were analyzed for TBA value and PH. Volatiles were steam distilled, volatilized at 6O"C, and 1 mL samples of headspace gas was analyzed using gas chromatography and mass spectrometry. Spectra for individual peaks on the total ion chromatograms were identified with spectra from known standards. Ground p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 29 publications
(20 reference statements)
9
55
1
3
Order By: Relevance
“…Coatings are often good oxygen barriers (Conca and Yang 1993) and can retard lipid oxidation in foods (Kester and Fennema 1986). Similar results were reported by Conca and Yang (1993), Kester and Fennema (1986), Krochta et al (1994) and Earle and McKee (1985) and Chidanandiah et al (2009) (Brewer et al 1992) that led to lipid oxidation. Dushyanthan et al (2000), Kumar and Sharma (2004), Chidanandiah et al (2009), Modi et al (2009, Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Phsupporting
confidence: 86%
“…Coatings are often good oxygen barriers (Conca and Yang 1993) and can retard lipid oxidation in foods (Kester and Fennema 1986). Similar results were reported by Conca and Yang (1993), Kester and Fennema (1986), Krochta et al (1994) and Earle and McKee (1985) and Chidanandiah et al (2009) (Brewer et al 1992) that led to lipid oxidation. Dushyanthan et al (2000), Kumar and Sharma (2004), Chidanandiah et al (2009), Modi et al (2009, Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Phsupporting
confidence: 86%
“…The mean values of the free fatty acids (FFA) increased significantly (P<0.05) throughout the storage period and a similar trend was observed by Anand et al (1991) oxidation and the production of volatile metabolites in the presence of oxygen attributed to oxygen permeability of packaging material (Brewer et al 1992). This was in agreement with the findings of Reddy and Rao (1997), Nag et al (1998), Singh and Verma (2000), Chidanandaiah et al (2009), Reddy et al (2009, Modi et al (2009), Kumar and Tanwar (2010), Sudheer et al (2010) and Bhat et al (2010) who also found a similar increase in TBARS values upon storage of different meat products.…”
Section: Free Fatty Acids (% Oleic Acid)supporting
confidence: 81%
“…Brewer et al (1992) concluded that significant quality deterioration could be expected during frozen storage of high and low fat, carrageenan extended beef patties. Gupta et al (1993) found reduced flavour scores in mutton and mutton+chicken sausages during refrigerated storage.…”
Section: Sensory Qualitymentioning
confidence: 99%